The Influence of Product Quality and Marketing on Consumer Purchase - Putriana Harahap; Midrawati Hasibuan; M. Rusdi Hasibuan (Quantitative Economics Journal, 2025)
This study aims to disclose proof empirical about impact from quality products and business marketing factory bakery house against interest buy Consumers. Population study This is consumer factory pinang city bakery house 2025. Technique of taking sample used is purposive sampling with amount sample as many as 54 respondents . Method analysis used For test hypothesis that is analysis regression multiple with SPSS application tool . Research results show that in a way partial quality product influential positive and significant to interest buy at the Pinang City bread house with mark t count 2.739 > 2.012 using level significance 0.034 < 0.05. Marketing efforts in a way partial influential positive as well as significant to interest buy consumers in Pinang City bakery house with results mark t count 2.246 > 2.012 using level significance 0.030 < 0.05. Variable quality products and business marketing influential simultaneous to interest buy consumers at the Pinang City bakery with F count result = 7.94 and F table = 3.191 using level significance of 0.0063 < 0.05.